Pengaruh Pemberian ZPT Ekstrak Kecambah Kacang Hijau dan Pestisida Nabati Ekstrak Lidah Buaya Terhadap Pertumbuhan Vegetatif Tanaman Tomat (Solanum lycopersicum) - Risti Wahyuni; M. Idris (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to determine the effects of various concentrations of growth regulators (ZPT) derived from mung bean sprout extract on the vegetative growth of Solanum lycopersicum, as well as the effect of aloe vera extract–based botanical pesticide on pest infestation intensity, either independently or in combination. The study employed a two-factor randomized block design consisting of ZPT concentrations (0%, 20%, 30%, 40%, 50%) and botanical pesticide concentrations (0%, 15%, 40%, 65%, 90%), each with three replications. The results showed that mung bean sprout extract–based ZPT significantly affected all vegetative growth parameters. The 50% concentration produced the greatest plant height (72.93 cm) and number of leaves (70.47), while the highest number of branches was obtained at the 20% (12.67) and 40% (12.53) concentrations. The botanical pesticide made from aloe vera extract significantly reduced pest infestation intensity, with the 65% and 90% concentrations classified as light damage (<25%), while the control (0%) showed very severe damage (>85%). The findings indicate that mung bean sprout–based ZPT effectively improves vegetative growth, and aloe vera–based botanical pesticide effectively suppresses pest attacks; however, their separate application is more optimal for achieving specific targets. Keywords: Pests, Botanical Pesticide, Vegetative Growth, Solanum lycopersicum, ZPT